iPSCs in tissue engineering - Birbrair, Alexander (Advances in stem cell biology, 2021)
"iPSCs in Tissue Engineering, Volume 11 addresses how induced pluripotent stem cells (iPSCs) are being used to advance tissue engineering. Somatic cells can be reprogrammed into iPSCs by the expression of specific transcription factors. These cells have been transforming biomedical research over the last 15 years. This book will address the advances in research of how iPSCs are being used for the generation of different tissues and organs such as the lungs, trachea, salivary glands, skeletal muscle, liver, intestine, kidney, even the brain, and much more"--Page 4 of cover.